Measurement of Polycyclic Aromatic Hydrocarbons in Baby Food Samples in Tehran, Iran With Magnetic-Solid-Phase-Extraction and Gas-Chromatography/Mass-Spectrometry Method: A Health Risk Assessment - Moazzen, Mojtaba; Shariatifar, Nabi; Arabameri, Majid; Hosseini, Hedayat; Ahmadloo, Mahsa (Frontiers in Nutrition, 2022)
Baby food is one of the most sensitive foods available, which is closely monitored for carcinogens. In this study, 16 PAH compounds were evaluated by using the method of MSPE/GC–MS (magnetic-solid-phase-extraction and gas-chromatography/mass-spectrometry). The recovery, LOD and LOQ of PAH compounds were 93.4–101.6%, 0.06-1.12 and 0.18-3.38 μg/kg, respectively. The outcomes indicated the mean of total PAHs in all samples was 3.73±0.8 µg/kg and the mean of BaP was 0.29±0.14 µg/kg that were lower than the US EPA standard level (1µg/kg, BaP in baby foods). Also, our results showed mixed five cereal-based baby food had maximum mean of ƩPAHs (5.06±0.68 µg/kg) and mixed wheat and date-based baby food had minimum mean of ƩPAHs (3.03±0.41 µg/kg). The carcinogenic risk due to PAH in the tested baby foods sold in Iran was adequately low, and all examined products were safe for consumers. Therefore, it can be said that the consumption of baby foods does not pose a threat to consumers.